Proses Kreatif Kelompok Karya Tutur Batin - Erviana, Vina; Lestari, Goesthy Ayu Mariana Devi; Setiawan, Afrizal Yudha (Jurnal Seni dan Pembelajaran, 2023)
Video mapping is a new course started in 2019. The Output of the Video Mapping course in 2019 is different from 2020. In the class of 2019, educational choreographic works were displayed through Youtube streaming, while the class of 2020 was in the form of dance performances with the concept of video mapping, one of which was the work of Tutur Batin. This study aims to describe the creative process of the Tutur Batin group. The research method used is descriptive qualitative. Data collection techniques using observation, interviews, documentation. The creative process of the Tutur Batin work group goes through the pre-production, production, post-production stages of Latief & Utud's (2015) theory. in video mapping. The pre-production stage determines the theme of the song Tutur Batin. The animation was edited using the CapCut application. Dancers were selected from group members, namely Komang Bela Safitri. The production stage compiled the animation according to the lyrics of the song Tutur Batin. Post-production stage, final editing exports 1080p (HD) resolution video. The dancer's movements are adjusted to the animation displacement adjusted to the lyrics of the song Tutur Batin.Keywords: Creative process, Video Mapping, Tutur Bati